Benchmarking Discount Rate in Natural Resource Damage Assessment with Risk Aversion. Issue 8 (6th June 2017) - Wu, Desheng; Chen, Shuzhen
Abstract : Benchmarking a credible discount rate is of crucial importance in natural resource damage assessment (NRDA) and restoration evaluation. This article integrates a holistic framework of NRDA with prevailing low discount rate theory, and proposes a discount rate benchmarking decision support system based on service‐specific risk aversion. The proposed approach has the flexibility of choosing appropriate discount rates for gauging long‐term services, as opposed to decisions based simply on duration. It improves injury identification in NRDA since potential damages and side‐effects to ecosystem services are revealed within the service‐specific framework. A real embankment case study demonstrates valid implementation of the method.